U źródeł polskiej naukowej metodyki literatury = At the Source of Polish Scientific Didactics of Literature - Lausz, Karol (Zielona Góra: Lubuskie Towarzystwo Naukowe)
This paper shows the progress in the work which has been done in literature didactics by the distinguished expert in Polish literature, Piotr Chmielowski. His work "The Didactics of the History of Polish Literature" ("Metodyka historii literatury polskiej") (published in 1889), is here the object of a very detailed interpretation. It was the first published help not only for the teachers but above all for the students studying literature and the history of literature. The author proved that "The Didactics" contains a gnestmany valuable didactic instructions and still remains useful, especially in the self-education process.
Keywords: metodyka; literatura polska - nauczanie